Adenoma metanéfrico: diagnóstico diferencial del carcinoma urotelial del tracto urinario superior. Reporte de un caso - David Andrés Castañeda Millán; Juan Camilo Álvarez Restrepo; Víctor Iván Romero Nieto; Diego Camacho Nieto; Wilfredo Donoso Donoso; Jorge Forero Muñoz (Case Reports)
Introduction: Metanephric adenoma is a rare benign kidney tumor. Patients with these tumors are usually asymptomatic, although polycythemia occurs in up 12% of cases. These masses are often described on diagnostic imaging as solid, single, well-defined, oval-shaped, unilateral lesions, located primarily in the renal medulla and without extrarenal involvement. These neoplasms are difficult to differentiate from malignant neoplasms of the upper urinary tract, so the definitive diagnosis is achieved by histopathology. Currently, the treatment of choice is radical nephrectomy.